A fluvial geomorphological study of river rehabilitation in the Kouga region, Eastern Cape - Pietersen, Adrian (Rhodes University, Faculty of Science, Department of Geography, 2009)
The Kouga Riparian Rehabilitation Project (KRRP) is seen as a pilot rehabilitation project in the Kouga region that is heavily invaded with Acacia mearnsii along the riparian zones of many mountain streams. Clearing of these black wattles and re-planting of indigenous vegetation are imperative to rehabilitation efforts. In this context, two invaded catchments were identified - the Baviaans and the Heuningnes. The aim of this research is to characterise the effects that the woody alien invasive Acacia mearnsii has had on the river channel morphology of the Baviaans and Heuningnes Rivers. A desktop and initial field analysis of the relevant study area catchments was completed. This was followed by a comparison of the channel morphology of the various study channel reaches using fixed channel transects. Ecological resource quality objectives (RQOs) for river rehabilitation from a fluvial geomorphological viewpoint were then established. A long-term monitoring protocol to assess whether or not these RQOs will be achieved was recommended. Follow-up channel transects were measured post wattle clearance in the Baviaans and short-term (<2yrs) changes in channel form were described. Differences in terms of the effect of Acacia mearnsii on channel form were then interpreted by direct comparison and through statistical analysis. Results indicate a number of significant differences between those channels impacted by black wattle infestation and those channels seen as unimpacted and natural. Short-term changes (<2yrs) that occurred within the study period post Baviaans wattle clearance were shown to be minimal for channel form as well as for bed material. The lack of any clear relationship or explanation between channel form and other channel controls suggests vegetation as the primary control. Vegetation, specifically the invasive alien vegetation, is the key controlling variable acting on channel form in the two study catchments.
Keywords: Fluvial geomorphology -- South Africa -- Eastern Cape; Alien plants -- South Africa -- Eastern Cape; Kouga Riparian Rehabilitation Project; Stream conservation -- South Africa -- Eastern Cape; Wattles (Plants) -- South Africa -- Eastern Cape; Riparian restoration -- South Africa -- Eastern Cape; Acacia mearnsii -- South Africa -- Eastern Cape; Kouga Region (South Africa); Kouga River (South Africa)